1977
DOI: 10.1007/bf00508808
|View full text |Cite
|
Sign up to set email alerts
|

Possible feed-back inhibition of noradrenaline release by purine compounds

Abstract: The contractile responses to transmural stimulation of, and the overflow of tritium from the rat portal vein prelabelled with 3H-noradrenaline were studied. The contractile responses of the rat portal vein were sustained throughout the period of stimulation. The tension developed did not decline when two consecutive periods of stimulation were compared. In contrast, the tritium overflow decreased during the second period of stimulation. Preincubation with 3 micronM phenoxybenzamine during 30 min increased 3-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

1980
1980
2003
2003

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(37 citation statements)
references
References 35 publications
4
32
1
Order By: Relevance
“…Adenosine in particular is a potent inhibitor of transmitter release (Ginsborg & Hirst, 1972;Hedqvist & Fredholm, 1976;Vizi & Knoll, 1976;Clanachan, Johns & Paton, 1977;Enero & Saidman, 1977;Hollins & Stone, 1979) and such an effect could explain this action of 4-AP whether or not the interaction occurs at the level of the potassium channel.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine in particular is a potent inhibitor of transmitter release (Ginsborg & Hirst, 1972;Hedqvist & Fredholm, 1976;Vizi & Knoll, 1976;Clanachan, Johns & Paton, 1977;Enero & Saidman, 1977;Hollins & Stone, 1979) and such an effect could explain this action of 4-AP whether or not the interaction occurs at the level of the potassium channel.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, adrenergic neurotransmission has been shown to be modulated by a number of other pharmacological agents including adenine nucleosides and nucleotides. Adenosine 5'-triphosphate (ATP) and adenosine selectively de-press the response to sympathetic nerve stimulation in several isolated blood vessels including rabbit portal vein (Su, 1978;Brown etal., 1982) and rat portal vein (Enero & Saidman, 1977;Wakade & Wakade, 1978;Moylan & Westfall, 1979;Enero, 1981). These compounds also inhibit sympathetic neurotransmission in various visceral preparations (see Burnstock & Brown, 1981 The portal vein receives a dense adrenergic innervation in the rabbit, rat and guinea-pig (Bumstock et al, 1979;Johansson et al, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…This action has been studied at both cholinergic (Ginsborg & Hirst, 1972; Ribeiro & Walker, 1975;Sawynok & Jhamandas, 1976;Vizi & Knoll, 1976;Gustafsson, Hedqvist, Fredholm & Lundgren. 1978) and adrenergic (Hedqvist & Fredholm, 1976;Clanachan, Johns & Paton, 1977;Enero & Saidman, 1977;Verhaeghe, Vanhoutte & Shepherd, 1977;Su, 1978;Paton, Bar, Clanachan & Lauzon, 1978) terminals in the peripheral nervous system. It has recently been concluded that adenosine can also reduce acetylcholine release at the synapse between motor axon collaterals and Renshaw cells (Lekic, 1977), and noradrenaline release from terminals in the cerebral cortex in vivo (Taylor & Stone, 1980) and in vitro (Harms, Wardeh & Mulder, 1978 (Bowery & Brown, 1974 …”
Section: Introductionmentioning
confidence: 99%